Amplicon‐based next‐generation sequencing: an effective approach for the molecular diagnosis of epidermolysis bullosa. (1st September 2015) - Tenedini, E.; Artuso, L.; Bernardis, I.; Artusi, V.; Percesepe, A.; De Rosa, L.; Contin, R.; Manfredini, R.; Pellacani, G.; Giannetti, A.; Pagani, J.; De Luca, M.; et al.
Summary: Background: Epidermolysis bullosa (EB) is caused by mutations in genes that encode proteins belonging to the epidermal–dermal junction assembly. Due to the extreme clinical/genetic heterogeneity of the disease, the current methods available for diagnosing EB involve immunohistochemistry of biopsy samples and transmission electron microscopy followed by single‐candidate gene Sanger sequencing (SS), which are labour‐intensive and expensive clinical pathways. Objectives: According to the recently published recommendations for the diagnosis and treatment of EB, the assessment of the mutational landscape is now a fundamental step for developing a comprehensive diagnostic path. We aimed to develop a customized, cost‐effective amplicon panel for the complete and accurate sequencing of all the pathogenic genes already identified in EB, and to minimize the processing time required for the execution of the test and to refine the analysis pipeline to achieve cost‐effective results from the perspective of a routine laboratory set‐up. Next‐generation sequencing (NGS) via the parallel ultra‐deep sequencing of many genes represents a proper method for reducing the processing time and costs of EB diagnostics. Materials and methods: We developed an EB disease‐comprehensive AmpliSeq panel to accomplish the NGS on an Ion Torrent Personal Genome Machine platform. The panel was performed on 10 patients with known genetic diagnoses and was then employed in eight family trios with unknown molecular footprints. Results: The panel was successful in finding the causative mutations in all 10 patients with known mutations, fully confirming the SS data and providing proof of concept of the sensitivity, specificity and accuracy of this procedure. In addition to being consistent with the clinical diagnosis, it was also effective in the trios, identifying all of the variants, including ones that the SS missed or de novo mutations. Conclusions: The NGS and AmpliSeq were shown to be an effective approach for the diagnosis of EB, resulting in a cost‐ and time‐effective 72‐h procedure.